Starting blocks-The biochemical basis of contraction-induced signal transduction in skeletal muscle: Starting blocks - Egan, B.; Newsholme, Philip (2012)
How does skeletal muscle adapt to regular exercise? This question has puzzled and enthused exercise physiologists for the best part of half a century since seminal work by John Holloszy demonstrated the remarkable plasticity of skeletal muscle in response to intense exercise training1. This phenomenon is overtly illustrated by the remodelling of muscle structure and function, with respect to muscular force, endurance and contractile velocity as a result of alterations in functional demand elicited by regular exercise2, or the ability of regular exercise to prevent or ameliorate pathophysiological disease states to which physical inactivity and skeletal muscle insulin resistance contribute3. © Biochemical Society.